The Comparative Analyses of Six Complete Chloroplast Genomes of Morphologically Diverse Chenopodium album L. (Amaranthaceae) Collected in Korea - Jongsun Park; Juhyeon Min; Yongsung Kim; Youngjae Chung (International Journal of Genomics)
Chenopodium album sensu stricto belonging to C. album aggregate is an annual cosmopolitan weed displaying the diversity of morphologies. We completed the six chloroplast genomes of C. album s. str. collected in Korea to understand the relationship between the diversity of chloroplast genomes and their morphological variations. All six C. album chloroplast genomes have a typical quadripartite structure with length ranging from 151,906 bp to 152,199 bp, similar to the previously sequenced C. album chloroplast genome (NC_034950). In total, 56 single nucleotide polymorphisms (SNPs) and 26 insertion and deletion (INDEL) regions (308 bp in total) were identified from the six chloroplast genomes, presenting a low level of intraspecific variations in comparison to the other angiosperm species. 376 normal simple sequence repeats were identified in all seven C. album chloroplast genomes. The phylogenetic analysis based on all available complete Amaranthaceae chloroplast genomes presents phylogenetic positions of six C. album samples as well as correlation with one of C. album morphological features. Our results provide the way to investigate intraspecific features of C. album chloroplast genomes and also the insights of understanding various intraspecific characteristics including morphological features.